Freedom of expression ... and its impact on the public - Abd Razak, Dzulkifli (2006)
The Danish Daily that caused so much turmoil internationally has finally offered a full page apology in a panArab newspaper last week. However, reportedly, it stopped short of explicitly saying sorry for printing the cartoons of Prophet Muhammad. Such an attitude is not a new phenomenon. Author Gai Eaton cited in his book, Islam and the Destiny of Man (1985), that this has been the case for at least 800 years when the Prophet was labelled as “the AntiChrist”. This has reminded on the European consciousness till today, observed Cambridgeeducated Eaton, who embraced Islam in 1951 before joining the British Diplomatic Service. He currently act as a consultant to the Islamic Culture Centre in London.